Pathological Stages of Abnormally Processed Tau Protein During Its Aggregation into Fibrillary Structures in Alzheimer’s Disease - García-Sierra, Francisco; Basurto-Islas, Gustavo; Jarero-Basulto, Jaime; Monroy-Ramírez, Hugo C.; Cruz, Francisco M. Torres; Callejas, Hernán Cortés; Rojas, Héctor M. Camarillo; Kristofikova, Zdena; Ripova, Daniela; Luna-Muñoz, José; Mena, Raúl; Binder, Lester I.; et al. (IntechOpen, 2011)
None